Neurostimulation as an Efficacious Nonpharmacologic Analgesic following Arthroscopic Rotator Cuff Repair - Ryan B. Juncker; Joel J. Gagnier; Faisal M. Mirza (Case Reports in Anesthesiology)
This case highlights the importance of pursuing nonpharmacologic analgesic modalities in orthopedic surgery to combat the current opioid epidemic. Presented is a patient who underwent an arthroscopic rotator cuff repair and biceps tenodesis operation and through the use of neurostimulation (in the form of auricular electrostimulation), fully recovered from surgery without the usage of any opioid or nonsteroidal anti-inflammatory medications. The patient was fitted with a novel auricular electrostimulation device (DyAnsys Primary Relief) in the immediate postoperative period that provided constant neurostimulation for 10 days, this neurostimulator was the only analgesic modality used in this case, and the patient reported minimal postoperative pain. The utility of this case centers around the lack of postoperative opioid use, presenting the idea that postsurgical orthopedic pain can be managed in a nonpharmacologic capacity, combatting the fields’ ongoing opioid epidemic.